Antireticulin antibody in systemic sclerosis. Issue 3 (March 1990) - Mahmud, T; Peakman, M; Senaldi, G; McWhirter, A; Black, C M; Vergani, D
Abstract : The prevalence, immunoglobulin class, and IgG subclass of antireticulin antibody in the serum samples of 32 patients with systemic sclerosis were investigated by indirect immunofluorescence on unfixed rodent tissue. Antireticulin antibody was present in 22/32 (69%) of patients and belonged to the IgG class in 19/22 (86%), the IgA class in 13/22 (59%), and the IgM class in 6/22 (27%) of positive sera. IgG1 was the predominant subclass of IgG antireticulin antibody, occurring either alone or in association with IgG3 in 12/19 cases (63%). Thus antireticulin antibody of the IgG and IgA classes is found in most patients with systemic sclerosis. The finding of an autoantibody with reactivity for collagen-like fibres in systemic sclerosis indicates that the antibody has a potential role in the pathogenesis of the disease, and as it belongs to the IgA class this suggests that it arises in response to antigens presented to the immune system at the mucosal level.